Gadolinium(III) Ion-Selective Electrode Based on 3-Methyl-1H-1,2,4-triazole-5-thiol - Hassan Ali Zamani; Hossein Behmadi (E-Journal of Chemistry)
The 3-methyl-1H-1,2,4-triazole-5-thiol (MTH) was used as a suitable ionophore for fabrication of a new gadolinium(III) ion selective potentiometric sensor. Nitrobenzene (NB) was used as plasticizing solvent mediator and sodium tetraphenyl borate (NaTPB) as an anion excluder. It displays a Nernstian response (19.8± 0.4 mV/decade) in the concentration range of 1.0×10-7 to 1.0×10-2 M with the detection limit of 7.3×10-8 M. The sensor has a very short response time (<10s) and can be used the pH range of 2.9-8.4. electrode was successfully applied as an indicator for gadolinium determination in titration with EDTA.